Penggunaan Tutor Sebaya dan Aktivitas Siswa untuk Meningkatkan Hasil Belajar Pokok Bahasan Analisis Isi Pidato Siswa Kelas VIII SMP Negeri 2 Tapung - Usman, Raja (GERAM, 2017)
The design of this research is Classroom Action Research (PTK). The purpose of this study is to improve the learning methods and student learning outcomes. Previously, there were still a few cases of low score of grade VII students of state Junior High School 2 (SMP Negeri 2) Tapung that is below the standard of Maximum Exhaustiveness Criteria (KKM). KKM has been determined by the school that is 70. the effort done either choosing the strategies or methods has been implemented, but not succeeded. From that point, the effort to improve the learning outcomes of teachers is by using peer methods. Through peer methods it is expected that their learning outcomes can increase because students feel free to express their opinions with peers and they do not feel reluctant and ashamed. This research was conducted with two cycles. Before conducting research the writer conducted survey. With the test, the purpose is to know how far the mastery of the students over the material given by the teacher. At the pre-cycle stage is complete score 24.00% and not complete 76.00%. In the first cycle, it increased to complete score 60.00% and incomplete 40.00%, while in the second cycle the score increased to 92.00% with complete score and incomplete one is 8.00%. According to the average of pre cycle rate of 61.00%, which is the first cycle is 78.00%, and the second cycle becomes 90.00% .thus it can be concluded that peer method can improve student learning outcomes at Junior High School 2 (SMP Negeri 2) Tapung.